Learning Disabilities and NF-1; MRI Abnormalities - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The significance of abnormalities on MRI was evaluated in 40 children with NF-1, aged 8 to 16 years, at the Children's Hospital, Sydney, Australia.